Inter-rater reliability of the extended Composite Quality Score (CQS-2) - Mickenautsch, Steffen; Rupf, Stefan; Miletić, Ivana; Strähle, Ulf Tilman; Sturm, Richard; Kimmie-Dhansay, Faheema; Vidosusić, Kata; Yengopal, Veerasamy (Frontiers in Medicine, 2023)
Aim To establish the inter-rater reliability of the Composite Quality Score (CQS-2) and to test the null hypothesis that it did not differ significantly from that of the first CQS version (CQS-1). Materials and methods Four independent raters were selected to rate 45 clinical trial reports using CQS-1 and CQS-2. The raters remained unaware of each other’s participation in this study until all rating had been completed. Each rater received only one rating template at a time in a random sequence for CQS-1 and CQS-2 rating. Raters completed each template and sent these back to the principal investigator. Each rater received their next template 2 weeks after submission of the completed previous template. The inter-rater reliabilities for the overall appraisal score of the CQS-1 and the CQS-2 were established by using the Brennan-Prediger coefficient (BPC). The coefficients of both CQS versions were compared by using the two-sample z-test. During secondary analysis, the BPCs for every criterion and each corroboration level for both CQS versions were established. Results The BPC for the CQS-1 was 0.85 (95% CI: 0.64–1.00) and for the CQS-2 it was 1.00 (95% CI: 0.94–1.00), suggesting a very high inter-rater reliability for both. The difference between the two CQS versions was statistically not significant (p = 0.17). The null hypothesis was accepted. Conclusion The CQS-2 is still under development, This study shows that it is associated with a very high inter-rater reliability, which did not statistically significantly differ from that of the CQS-1. The promising results of this study warrant further investigation in the applicability of the CQS-2 as an appraisal tool for prospective controlled clinical therapy trials.